2021
DOI: 10.1186/s12885-021-09032-8
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated radiotherapy in ten fractions for postmastectomy patients: a phase II study compared with another hypofractionation schedule with sixteen fractions

Abstract: Background The purpose of this phase II study was to evaluate the feasibility of hypofractionated radiotherapy (HFRT) with a dose of 36.5 Gy in 10 fractions in postmastectomy patients. Methods From March 2014 to December 2015, 85 patients with locally advanced breast cancer were eligible to participate in this study with a schedule of 36.5 Gy in 10 fractions. Intensity-modulated radiation therapy (IMRT) was delivered to the chest wall with or witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…Indeed, the incidence of grade 2 or higher acute dermatitis in patients treated with a HF regimen varied from 5 to 27% in most studies, which is consistent with the 10.7% incidence found in our study. In all these studies, the comparison between the HF and CF groups showed a 2 to 3-fold decrease in acute skin toxicity with hypofractionation, which is also comparable to our results [8,9,[15][16][17]. Arsenault et al went further by also analyzing the duration of acute skin injury, and presented as n/n T (%) unless otherwise specified.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, the incidence of grade 2 or higher acute dermatitis in patients treated with a HF regimen varied from 5 to 27% in most studies, which is consistent with the 10.7% incidence found in our study. In all these studies, the comparison between the HF and CF groups showed a 2 to 3-fold decrease in acute skin toxicity with hypofractionation, which is also comparable to our results [8,9,[15][16][17]. Arsenault et al went further by also analyzing the duration of acute skin injury, and presented as n/n T (%) unless otherwise specified.…”
Section: Discussionsupporting
confidence: 91%